Shear History Effect on the Viscosity of Carbon Nanotubes Water-based Nanofluid - Estelle, Patrice; Halelfadl, Salma; Doner, Nimeti; Mare, Thierry (Current Nanoscience, 2013)
Experimental results on the steady-state rheological behaviour of carbon nanotube (CNT) water-based nanofluid are presented. We have investigated the influence of a controlled preshear history on the viscosity of CNT water-based nanofluid. Two types of preshear history effect are studied: the influence of stress rate during preshear and the effect of resting time before viscosity measurement. It is revealed that CNT water-based nanofluid behaves as a viscoelastic media at low shear rate and it is shear-thinning at higher shear rate. This behaviour is strongly dependent on shear history due to the breakdown in the structural network of nanofluid agglomerates. It is also observed that the nanofluid can reform at rest after preshear following the resting time and the rate or preshear applied to the nanofluid.
Keywords: nanofluid